Pengaruh laba, ukuran perusahaan dan komponen akrual terhadap arus kas aktivitas operasi masa depan pada perusahaan wholsale and retail yang terdaftar di bursa efek Indonesia periode 2008-2012 - Rahmania '; Rasuli '; Al-azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine the effect of earnings, firm size and components of accruals on cash flow operating activities in the future Wholesale and Retail companies listed in Indonesia Stock Exchange 2008-2012 period.The population in this study is the Wholesale and Retail are listed in the Indonesia Stock Exchange (BEI) in the period 2008-2012, amounting to as much as 30 perusahaan.Sampel used in the study were 30 perusahaan.Teknik sampling used in this study is the purposive criteria sampling.Adapun in this study include wholesale companies and retail has been listed on the Indonesia Stock Exchange in the study period 2008-2012. The data used are secondary data obtained from the Indonesia Stock Exchange in particular from the Indonesian Capital Market Directory (ICMD)The results showed that a significant difference between Income, Accounts Receivable, Depreciation and Debt to Cash Flow Operating Activities Future Wholesale and retail company. While the size of the Company and the Stock is not a significant influence on Future Cash Flows Operating Activities Depanpada Wholesale and retail companies.Keywords: Income, Accounts Receivable, Depreciation Expense, Debt, Inventory, Operating Cash Flow